ANALISIS MINAT MENABUNG PADA BANK SYARIAH - Luthfiardhany (2022)
Saving is an act of saving funds for the future. Saving means that we have prepared for unexpected needs in the future. Interest in saving is an encouragement for someone to deposit their funds in a bank whose withdrawals can only be made according to certain conditions as agreed between the bank and the customer. Sharia Bank is a bank that carries out its business activities based on sharia principles. Interest in saving in Islamic banks is still low when compared to conventional banks. This study analyzes the interest in saving at Islamic banks. This can prove that people who save at Islamic banks and are interested in saving at Islamic banks are still few.